Canalized urban rivers: The Biriguizinho Stream, in Birigui/SP - Zanateli, Jéssica Telles; Constantino , Norma Regina Truppel (Electronic Journal "Fórum Ambiental da Alta Paulista", 2021)
The Biriguizinho Stream, like so many other urban rivers, has undergone changes over the years, with the correction of its banks, channeling and suppression of its source. These measures were seen as the most adequate to enable the urban growth of Birigui-SP. However, with the passage of time and expansion without predetermined guidelines, episodes of flooding occur in the region of the aforementioned stream, overloaded with the runoff of rainwater from a large part of the city. The purpose of this article is to analyze the factors that contribute to flooding on the banks of the Biriguizinho stream, in the city of Birigui/SP, with the aim of proposing green infrastructure solutions that mitigate or definitively affect floods, avoiding risky situations. The methodological procedures adopted include readings on the themes of urban rivers, landscape, perception, risks, and green infrastructure, in addition to observation of the study area.